“This is not science. This is storytelling:” The Poetics of Science in Arcadia - Liliane Campos (Sillages Critiques)
After using catastrophe theory and quantum mechanics in his earlier texts Professional Foul and Hapgood, Stoppard borrows some of Arcadia’s key concepts from thermodynamics and chaos theory. This article explores the strong epistemological continuity of Stoppard’s references to science, which provide him with metaphors for the systematic instability of knowledge asserted by his plays. The analysis focuses on the poetic use of entropy, unpredictable determinism and iteration in Arcadia, and their structuring role as metaphors of emplotment. Within the dialogue, the evocation of these concepts follows an ekphrastic pattern, strengthening the play’s reflection on the relation between art, time and mimesis.